Application of Material Law in Islamic Banking Disputes Following Constitutional Court Decision No. 93/PUU-X/2012: A Review of Normative-Jurisprudential Literature: Penerapan Hukum Materiil Sengketa Perbankan Syariah Pasca Putusan MK No. 93/PUU-X/2012: Tinjauan Literatur Normatif-Yurisprudensial - Fatimah, Sitti; Ludfi, Ludfi (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This study examines the application of material law in resolving Islamic banking disputes following the Constitutional Court Decision No. 93/PUU-X/2012 through a review of normative-jurisprudential literature. The Constitutional Court's decision affirmed the absolute authority of religious courts in Islamic banking disputes, but the practice of applying material law by judges shows problematic dynamics. The objectives of this study focus on three things: the consistency of judges' normative references, the dominant sources of material law used, and the suitability of their application to the principles of maqashid al-shariah. The method used is normative juridical with a literature approach, which involves a review of laws and regulations, court decisions, DSN-MUI fatwas, the Compilation of Islamic Economic Law (KHES), and relevant academic documents. The results of this study indicate that although the authority for dispute resolution has formally shifted to religious courts, the application of substantive law in practice remains inconsistent with the ideals of Islamic economic law. Judges tend to rely more on the Civil Code as the primary reference, while the KHES and DSN fatwas are used to a limited extent and are more complementary. Furthermore, the substance of decisions still relies heavily on a formalistic approach, so that the values of maqashid al-shariah, such as justice, benefit, and protection of rights, have not been optimally internalized. Theoretically, this study enriches the discourse on the importance of integrating maqashid al-shariah into the practice of Islamic economic jurisprudence. Practically, these findings imply the need to strengthen the capacity of judges through training, the development of more applicable technical guidelines, and the strengthening of the position of KHES and DSN fatwas as primary sources of law, in order to realize a more substantive, just, and beneficial sharia justice system